Antihypertensive Effect of Perla and Esmeralda Barley (Hordeum vulgare L.) Sprouts in an Induction Model with L-NAME In Vivo - Abigail García-Castro; Alma D. Román-Gutiérrez; Fabiola A. Guzmán-Ortiz; Raquel Cariño-Cortés (Metabolites)
Background: Hypertension is one of the leading causes of premature death worldwide. Despite advances in conventional treatments, there remains a significant need for more effective and natural alternatives to control hypertension. In this context, sprouted barley extracts have emerged as a potential therapeutic option. This study presents the evaluation of the bioactive properties of extracts from two varieties of barley germinated for different periods (3, 5, and 7 days), focusing on their potential to regulate blood pressure mechanisms. Objectives/Methods: The main objective was to assess the effects of these extracts on blood pressure regulation in N(ω)-Nitro-L-Arginine Methyl Ester (L-NAME)-induced hypertensive rats. Renal (creatinine, urea, uric acid, and total protein) and endothelial (NOx levels) function, angiotensin-converting enzyme (ACE) I and II activity, and histopathological effects on heart and kidney tissues were evaluated. Results: In particular, Esmeralda barley extract demonstrated 83% inhibition of ACE activity in vitro. Furthermore, the combined administration of sprouted barley extract (SBE) and captopril significantly reduced blood pressure and ACE I and II activity by 22%, 81%, and 76%, respectively, after 3, 5, and 7 days of germination. The treatment also led to reductions in protein, creatinine, uric acid, and urea levels by 3%, 38%, 42%, and 48%, respectively, along with a 66% increase in plasma NO concentrations. Conclusions: This study highlights the bioactive properties of barley extracts with different germination times, emphasizing their potential health benefits as a more effective alternative to conventional antihypertensive therapies.